Integrated Library Management System - Inbavalli, M; Chandana, A (International Journal of Computer Sciences and Engineering, 2025)
An integrated library management system (ILMS) is a computer based system that is used for monitoring the daily activities of a library. The ILMS manages borrowing and returning of books and other resources. It helps users for finding resources for teaching, reading and learning. The ILMS system is maintained by the librarian and library admin. The ILMS stores details like name, address, ID number, date of birth of members working in library and users who come to library. The ILMS provides exact information about the number of books that are taken by the users. This system can view reserve books and find out who is having that book. The Integrated Library Management System (ILMS) uses a fingerprint scanning for securing the datas stored in the library database. The fingerprint scanner is also called as Direct Fingerprint Reader (DFR).The ILMS contains several modules. The ILMS minimizes the redundancy of data, secures the data and provides fast transaction to the users.